A business plan review for Moçambique Previdente, SGFP, SA - Bila, Ilidio Rodrigues (My University, 2018)
Moçambique Previdente, SGFP, SA (MP, SGFP) is a pension fund management firm, operating in Mozambique, since 2013. The shareholders previously ordered a study for a business plan that could set the long-term strategy and feasibility study for the company. This study was conducted in 2011 by Pricewaterhouse Coopers (PwC), Mozambique, in conjunction with Envision Strategy Consultants (ESC). The 2012 macroeconomic conditions were favourable, as the economic outlook was positive amid discoveries of vast reserves of natural gas in the country. Mozambique experienced an average GDP growth rate of 7.2% between 2001 and 2015. This rate was 2.3% higher than the average GDP growth rate in the Sub-Saharan region for the same period (The World Bank, 2017)1. PwC & ESC (2011) projected that the assets under management (AUM) by MP, SGFP would be close to USD39.9 million by the fourth year, as opposed to the USD2.5 million (minus fees, insurance and other expenses) recorded in 2016. The total number of participants predicted for the fourth year was 17.7 thousand, as opposed to the 1.3 thousand participants enrolled by 2016. Note that until 2016, the pension fund business comprised only 6.7 thousand participants (Instituto de Supervisao de Seguros de Mocambique, 2017). In recent years, the current macroeconomic environment became a matter of concern as the country was going through a financial crisis (Cotterill, 2017). It was with the current state of the industry in mind that the company decided to draft a new business plan. The report used a mixed methodology to capture all dimensions of the problem. So, it conducted a market survey to get an indication of pension fund service attributes clients would value the most with. The results could help improve the value proposition 1 Own calculations derived from The World Bank Data Bases, https://data.worldbank.org/?name_desc=true 2 and increase market share. The report also used audited results and other documents available on the public domain to understand other aspects influencing business performance. The report estimated that business volumes could grow close to MZN107.6 million in five (5) years, and that would lead to a fair value of the equivalent MZN133.5 million. The book value of equity was estimated to be close to MZN33.12 million in 2017. The close monitoring of expenditures and gains of efficiency proved to be determinant to improve profitability issues. The improvement of the firm’s cash flow would be dependent on the Board member’s ability to renegotiate and restructure ADM (Aeroportos de Moçambique, EP) debt, and the management aptitude to diversify from State-Owned Enterprises (SOEs) and add more privately controlled corporate clients. These clients would ideally act in more resilient industries like the financial, extractive and energy sector. The practical deployment of profit centres and the hiring of an experienced business developer were also pivotal to the strategy to be adopted. All the above will not matter if concrete actions do not follow recommendations, and policies to address accountability issues and good governance is not in place and enforced.
MBA
Keywords: Pension trusts -- South Africa -- Management. Pension trusts -- Investments. Institutional investments -- Social aspects.